Change Management Models: Commonalities and Key Challenges in the Industry (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
It can be argued that managing change is crucial for any organisation to survive and succeed in the present highly competitive and continuously evolving business environment. However, theories and approaches to change management currently available to academics and practitioners are often contradictory, mostly lacking empirical evidence and supported by unchallenged hypotheses concerning the nature of contemporary organisational change management. This paper seeks to understand the key challenges faced when implementing change management projects in the industry, especially in aerospace, and the commonalities across existing change management methodologies. The paper describes results from interviews with industry experts and the literature review to provide a discerning sight of the challenges faced when implementing change management projects and the components shared by the available methodologies.